2022
DOI: 10.3390/educsci12110811
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence Heuristic and Filter-Empowerment Heuristic: Investigating the Reversed Gender Achievement Gap in a Sample of Secondary School Students in Saudi Arabia within the Framework of Educational and Learning Capital

Abstract: The reversed gender achievement gap in the Kingdom of Saudi Arabia (KSA) in favor of girls developed in a societal environment that still predominantly favors men. The finding illustrates how equity gaps at higher systemic levels may not translate seamlessly to lower systemic levels. We propose that this lack of correspondence between systemic levels regarding equity gaps can be explained by the fact that more exogenous learning resources (educational capital) selectively reach girls’ actiotopes, enabling them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
0
5
1
Order By: Relevance
“…The findings of this investigation illuminate that gender parity in remuneration is maintained within the healthcare sector, which has positively impacted female workers’ satisfaction, but such a revelation is contrary to previous reports indicating significant pay gaps between women and men. 21 , 22 However, such inconsistency between this study’s findings and previously reported data on gender pay gaps may be explained based on the industry-specific improvements. Subsequently, it becomes affirmative to allude that the Saudi healthcare sector may be outperforming other sectors in terms of pushing for fair and equitable remuneration for women, but such hypotheses may require sector-specific comparisons if plausible inferences were to be made.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The findings of this investigation illuminate that gender parity in remuneration is maintained within the healthcare sector, which has positively impacted female workers’ satisfaction, but such a revelation is contrary to previous reports indicating significant pay gaps between women and men. 21 , 22 However, such inconsistency between this study’s findings and previously reported data on gender pay gaps may be explained based on the industry-specific improvements. Subsequently, it becomes affirmative to allude that the Saudi healthcare sector may be outperforming other sectors in terms of pushing for fair and equitable remuneration for women, but such hypotheses may require sector-specific comparisons if plausible inferences were to be made.…”
Section: Discussioncontrasting
confidence: 84%
“…The results of this study reveal invaluable insights on how women worker’s satisfaction levels may have a bearing on equality when it comes to remuneration, which reflects Stoeger et al’s call on parity in salaries, wages, or allowances as key for women’s perception on women empowerment. 22 It should be recalled that one of the key motivations to work is remuneration, which implies that when one is satisfied that they are well remunerated, the potential for them to be satisfied and work hard increases. The findings of this investigation illuminate that gender parity in remuneration is maintained within the healthcare sector, which has positively impacted female workers’ satisfaction, but such a revelation is contrary to previous reports indicating significant pay gaps between women and men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when focusing on a specific and seemingly well‐defined equity gap such as the gender payment gap in medicine, it quickly becomes clear that many further methodological refinements are necessary, for example, regarding country or employment, among other factors 88–90 . Further complicating the picture is the phenomenon of reversed equity gaps, that is, a possible reversal of a typical pattern of inequality 91,92 . Thus, it seems as if each equity gap has its own unique biography, characteristics, and diversity.…”
Section: Inequalities and Equity Gaps In Stemm Talent Developmentmentioning
confidence: 99%
“…[88][89][90] Further complicating the picture is the phenomenon of reversed equity gaps, that is, a possible reversal of a typical pattern of inequality. 91,92 Thus, it seems as if each equity gap has its own unique biography, characteristics, and diversity. This, of course, complicates the conceptualization of a unified umbrella concept.…”
Section: Inequalities and Equity Gaps In Stemm Talent Developmentmentioning
confidence: 99%